Artist featured (Raton Range Raton, NM, 1980)
Article is about M. Emerson Nigh.
Newspaper article
Mater List Item # 14
File location is in the Raton File Cabinet
Keywords: Nigh, M. Emerson; Nigh, Frank; New Mexico State Fair; Announcement; Local Artist; Oil Painting; State Fairs; Fine Arts Competion; Raton, New Mexico